Implementasi Komik Digital Interaktif Berbasis Al Islam dan Kemuhammadiyahan dalam Pendidikan Karakter di Sekolah Dasar - Nita Widyakusuma; Dien Nurmarina Malik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article discusses the implementation and innovation of an interactive digital comic titled “Si Panca dan Kekuatan Norma,” designed as a character education tool that integrates Islamic and Muhammadiyah values (AIK) for elementary school students. The research uses a descriptive-qualitative approach involving 25 fifth-grade students from SDN Padurenan II. The digital comic, developed through Canva and supported by reflective quizzes via Quizizz, presents moral dilemmas faced by a student named Panca in daily life situations. The content emphasizes values such as honesty, discipline, responsibility, and social care. The media was implemented over four learning sessions and evaluated through observation, teacher interviews, student questionnaires, and quiz results. Initial findings show that the comic successfully improved student participation, moral awareness, interpersonal interaction, and understanding of AIK values. The media also fostered a joyful, contextual, and interactive learning environment. This study highlights the potential of digital storytelling to support Islamic character development and recommends its broader application in Islamic-based education.